My Stage:Participatory Theatre with Immigrant Women as a Decolonizing Method in Art-based Research - Mikkonen, Enni; Hiltunen, Mirja; Laitinen, Merja (2020)
This article discusses how art-based research can function as a decolonizing research method. Its analysis is based on the collaboration of social work and art education disciplines for advancing social justice and deconstructing power dominances. Empirically, the research builds on a participatory theatre project, “My Stage,” with immigrant women. The project was established as part of a larger interdisciplinary project, “Art Gear,” in Northern Finland, which promoted the bidirectional integration of the local population and people with immigrant backgrounds. The research data were collected through participatory observation and reflective discussions by the social work researcher in the theatre workshops. By the analysis of an interdisciplinary team of social work and art education researchers, we develop a context-sensitive framework of art-based research to advance decolonizing research methods, which contribute to supporting the agency and inclusion of marginalized populations in research and in their integration processes at times of complex and rapid demographic and societal changes.